2019
DOI: 10.7150/thno.33114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum extracellular vesicles as noninvasive diagnostic markers of glioma

Abstract: Rationale : Glioma is the most common malignant primary brain tumor in the central nervous system (CNS). The lack of reliable noninvasive diagnostic and prognostic methods is one of the main reasons for the high mortality of glioma. Serum has become a useful biomarker for the diagnosis and prognosis prediction of glioma because extracellular vesicles (EVs) carry molecular components from their parental cells. Methods : To detect EVs and perform molecular analysis of serum EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 72 publications
1
40
0
5
Order By: Relevance
“…Sampling was performed at the Q3 time point (i.e., the third quarter of the first year after diagnosis, 6–9 months after the initiation of primary radiotherapy and chemotherapy) for 54/55 patients and in the fifth month for one patient. Consistent with previous results [ 21 ], serum from glioblastoma patients showed a much higher concentration of small EVs (size range: 87–166 nm) compared to HV when they were isolated by using size-exclusion chromatography (SEC, Figure 1 A). In order to specifically isolate relevant glioblastoma-associated EVs, we subsequently performed immunoprecipitation using CD44 (SEC + CD44), which we had previously identified in a screen of serum EV proteins as being important in tumor progression [ 18 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Sampling was performed at the Q3 time point (i.e., the third quarter of the first year after diagnosis, 6–9 months after the initiation of primary radiotherapy and chemotherapy) for 54/55 patients and in the fifth month for one patient. Consistent with previous results [ 21 ], serum from glioblastoma patients showed a much higher concentration of small EVs (size range: 87–166 nm) compared to HV when they were isolated by using size-exclusion chromatography (SEC, Figure 1 A). In order to specifically isolate relevant glioblastoma-associated EVs, we subsequently performed immunoprecipitation using CD44 (SEC + CD44), which we had previously identified in a screen of serum EV proteins as being important in tumor progression [ 18 ].…”
Section: Resultssupporting
confidence: 92%
“…Many studies have identified microRNAs in the biofluids (e.g., cerebrospinal fluid (CSF), serum and plasma) of patients with glioblastoma, which can be EV-independent [ 19 ] or contained in EVs [ 20 ]. While some reports have demonstrated the upregulation of microRNAs in patients with high-grade glioma compared to low-grade glioma [ 21 ], no report has thus far shown the potential of microRNAs in biofluids to stratify patients into different prognostic groups at critical time-points during treatment. Moreover, it is unknown whether the detection of any relevant microRNAs in the serum of glioma patients can be enhanced through specifically capturing tumor-derived EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Although exosomal cargo specificity varies according to the parent cell-type and other environmental conditions (e.g., local temperature [69], O 2 content [70,71], and pathological state [72][73][74]), there are numerous proteins highly associated with exosomes (including heat shock 70 kDa protein 8 (HSPA8), CD9, glyceraldehyde 3-phosphate dehydrogenase (GAPDH), beta actin (ACTB), CD63, CD81, annexin A2 (ANXA2), enolase 1 (ENO1), heat shock protein HSP 90-alpha (HSP90AA1), elongation factor 1-alpha 1 (EEF1A1), pyruvate kinase isozyme M2 (PKM2), 14-3-3 protein epsilon (YWHAE), syntenin-1 (SDCBP), programmed cell death-6 interacting protein (PDCD6IP), serum albumin (ALB), 14-3-3 protein zeta (YWHAZ), eukaryotic elongation factor 2 (EEF2), gamma actin (ACTG1), lactate dehydrogenase A (LDHA), heat shock protein HSP 90-beta (HSP90AB1), aldolase A (ALDOA), moesin (MSN), annexin A5 (ANXA5), phosphoglycerate kinase 1 (PGK1), and cofilin 1 (CFL1) [75]. The aforementioned characteristics, along with their unique mechanism of actions, make exosomes of immense biological interest, as testified by the plethora of studies aimed at employing them both as non-invasive diagnostic biomarkers [76][77][78][79][80] and as biological delivery systems [81][82][83][84].…”
Section: Brief Overview Of Evs and Exosome Biologymentioning
confidence: 99%
“…В то время как нормальные клетки секретируют микровезикулы и экзосомы, апоптотические тела образуются только во время запрограммированной клеточной гибели, которая, как и во многих опухолях, играет важную роль в патофизиологии глиобластомы [18]. Высвобождаемые клетками глиобластомы ВВ содержат широкий спектр молекул, включая нуклеиновые кислоты и белки, отражающие специфические молекулярные признаки клеток первичной опухоли, и изменяются в процессе лечения [19][20][21], при этом липидная мембрана защищает внутреннее содержимое ВВ от ферментной деградации [18,22]. Было показано, что ВВ из клеток опухоли пересекают интактный ГЭБ и обнаруживаются в крови пациентов с глиобластомой [15].…”
Section: Introductionunclassified
“…Позднее H. Wang и соавт. [22] сравнили уровень экспрессии EGFR во ВВ сыворотки 23 пациентов с глиомами различной степени злокачественности (5 пациентов с глиобластомой). Парные сравнения экспрессии EGFR в образцах, взятых до хирургического лечения и через 1 нед после операции у 8 пациентов, показали достоверное снижение экспрессии EGFR после удаления опухоли в каждом случае (р <0,05).…”
Section: Introductionunclassified